As nossas Áfricas: população escrava e identidades africanas nas Minas Setecentistas - Rodrigo Castro Rezende (2006)
This Thesis attempts to analyze the ethnic composition and identities of African slaves in Minas Gerais during the eighteenth century. In order to do so the slave trade into the captaincy is examined since, first, a focus on the effects of supply and demand allows for a better understanding of ethnic make up and, second, the relationships built up among the Portuguese and Luso-Brazilians in Africa had a direct influence on representations attributed to slaves in Minas. Thus, certain African nations (nações) took on representations which made them to be seen as either culturally closer to Luso-Brazilians or more apart. It was not unusual for these representations to express a worldview of the self. That is to say that, in fact, they expressed how the non-African came to understand diverse African cultural codes and values. On the other hand, Africans appropriated these same representations, assuming them within the Minas society for, whatever their real desires, they were forced to adapt to their new reality. In other words, in appropriating these representations Africans constructed their identities of survival. It should be emphasized, however, that African cultural codes and values did not disappear upon making contact with the non-African. These codes and values, referred to here as historical identitities, were never de-codified by non-Africans, thus allowing for African individuals to express their identities in a more autonomous form than the specialized historiography admits. In that sense it can be posited that the so-called process of acculturation was a mere invention, given that there were multiple eighteenth-century African identities in Minas each of which manifested itself in distinct fashion depending upon the circumstances.